Impactos atmosféricos das transformações territoriais e do crescimento do agronegócio na Amazônia matogrossense - Andrea Cavicchioli; Ericka Pardini Morrone; Rodrigo Marques; Adalgiza Fornaro (Confins)
The State of Mato Grosso, in the west-central part of Brazil, has undergone over the last two decades a severe process of land transformation with the opening of large agricultural areas to the detriment of tropical forest and savannahs. This deforestation process is largely associated to the production of soybeans: in 2005, the soybean-cultivated area surpassed 6.1 mi hectares with an overall production of 17.76 mi tons. Then, there is little doubt that agribusiness can be regarded as one of the drivers of the increase in biomass burning fires in this State, where a record peak was so far document in September 2004 with almost 25000 occurrences – 35% of all fires detected in Brazil in the same month. Biomass burning is typical tropical phenomenon and, on account of it, millions of tons of gases and particulate matter (PM) are launched into the atmosphere every year. These emissions cause negative impacts that encompass effects on human health and alterations in the energetic balance of the atmosphere associated with climatic changes on a regional and global scale. Although estimations on the concentration of PM can be obtained from mathematical modeling based on remote sensing, in situ monitoring is fundamental. The present study aimed at collecting primary data on fine and coarse PM concentration and composition in the agricultural area of Mato Grosso. To this purpose, samples were collected in the municipalities of Guarantã do Norte, Juara, Feliz Natal, Sinop and Sorriso, between September and October 2009. These sampling points were selected during a preliminary exploratory field trip in the State in July 2009 (“Knowing Amazonia and the territorial dynamics of Mato Grosso”) within the framework of the year of France in Brazil. Sinop, Sorriso and Guarantã do Norte are localised on the main State’s motorway (BR163), whereas Feliz Natal and Juara lay, respectively, on the east and west sides of this axis and close to the deforestation line. For comparative purposes, samples were also collected in Cuiabá and Rondonópolis, the main urban centres of the State. Analyses included the gravimetric determination of the PM concentration, the quantification of black carbon (by reflectance spectroscopy) and the elemental composition (by energy-dispersion X-ray fluorescence).